一种基于多重交叉验证的桥梁损伤识别方法 (2021)
本发明的一种基于多重交叉验证的桥梁损伤识别方法，包括在桥梁下方沿桥梁延伸方向连续布置n个分布式长标距光纤光栅传感器；将所有传感器连接到解调设备，采集车辆经过时桥梁的长标距应变响应；对所有传感器进行排列组合，以任意三个传感器为一组，将对应得到的长标距应变做组内二阶差分；求每组应变差分曲线与时间横轴包围的面积；统计在阈值范围外异常的损伤指标S*所关联的传感器编号；带入损伤计算公式，得到结构损伤程度β。本发明通过多重交叉验证避免了个别传感器的异常和随机性，得到的结果置信度高，同时传感器耐久性更强，精度高，适用于简支梁和连续梁结构桥梁，可实现低成本大范围应用，及时发现桥梁潜在损伤，避免事故发生。 The invention discloses a bridge damage identification method based on multiple cross validation. The method comprises the following steps that: continuously arranging n pieces of distributed long-gauge-length fiber grating sensors along a bridge extension direction below a bridge; connecting all sensors to demodulation equipment to collect the long-gauge-length strain response of the bridge whena vehicle passes; carrying out permutation and combination on all sensors, taking any three sensors as a group, and carrying out intra-class second order difference on the correspondingly obtained long-gauge-length strain; solving an area surrounded by each group of strain difference curves and a time horizontal axis; carryin